Experimental and Numerical Analysis of Woven Bamboo and Jute Fiber Reinforced in Epoxy Composites - Radhakrishna Kumshikar; R. Shankara Reddy (Mechanics of Advanced Composite Structures)
Aerospace, transportation, marine, and space applications demand structural materials with low densities yet strong, hard, and high impact strength. Composites are materials that satisfy the needs of recent technology. Composites are flexible materials that meet the demands of modern technologies. Herbal fibers may be processed and need little energy. Using natural fibers as reinforcement in polymer composites to create inexpensive building materials has recently gained popularity. The experimental and FEA analysis of woven bamboo and jute fiber reinforced in epoxy composites is the main emphasis of the current work. Mechanical properties such as tensile and flexural properties are evaluated for various stacking sequences. Also, numerical analysis is done using licensed Hyper mesh software. The S1 stacking sequence's testing findings had the highest tensile strength (47.411 MPa) and tensile modulus (695.44 MPa). Additionally, it has the highest flexural strength and modulus at 80.25 MPa and 9.065 GPa, respectively. FEA results deviate by more than 10%. Excellent mechanical characteristics are achieved with a fiber volume fraction of 10% bamboo, 20% jute, and 70% matrix material. The SEM images showed the composite’s interface breakdown between the textiles' layers.